2020
DOI: 10.1136/bmj.m456
|View full text |Cite
|
Sign up to set email alerts
|

Associations of habitual fish oil supplementation with cardiovascular outcomes and all cause mortality: evidence from a large population based cohort study

Abstract: Objectives To evaluate the associations of habitual fish oil supplementation with cardiovascular disease (CVD) and mortality in a large prospective cohort. Design Population based, prospective cohort study. Setting UK Biobank. Participants A total of 427 678 men and women aged between 40 and 69 who had no CVD or cancer at baseline were enrolled between 2006 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 48 publications
3
47
1
Order By: Relevance
“…In this context, the causal effect of obesity on nearly all specific cardiovascular outcomes suggested in this study provides an enthusiastic prospect in which lifestyle modification to reduce adiposity can result in the overall reduction of cardiovascular health problems and substantial health-economic burden 86 . This study supports the assertions that reducing adiposity through interventional approaches, such as bariatric surgery 87 ; promotion of educational equality 88 ; lifestyle modifications, including healthy diets [89][90][91][92][93][94] ; and increasing physical activities 93 may provide a better chance of improving one's well-being 95 , even more so than previously expected, by affecting multiple vascular health outcomes. Our results also support the diet and lifestyle recommendation proposed by the American Heart Association (AHA) 96 , and further specify the benefits.…”
Section: Clinical Implications and Future Researchsupporting
confidence: 83%
“…In this context, the causal effect of obesity on nearly all specific cardiovascular outcomes suggested in this study provides an enthusiastic prospect in which lifestyle modification to reduce adiposity can result in the overall reduction of cardiovascular health problems and substantial health-economic burden 86 . This study supports the assertions that reducing adiposity through interventional approaches, such as bariatric surgery 87 ; promotion of educational equality 88 ; lifestyle modifications, including healthy diets [89][90][91][92][93][94] ; and increasing physical activities 93 may provide a better chance of improving one's well-being 95 , even more so than previously expected, by affecting multiple vascular health outcomes. Our results also support the diet and lifestyle recommendation proposed by the American Heart Association (AHA) 96 , and further specify the benefits.…”
Section: Clinical Implications and Future Researchsupporting
confidence: 83%
“…Other metaanalyses, reviewed together with the cohort studies, mostly show reductions in blood pressure only in hypertensive subjects (Colussi et al, 2017). Consistent with this, a recent cohort study (which did not focus on blood pressure) found an overall reduced cardiovascular disease incidence and cardiovascular disease-related mortality in individuals habitually taking supplements where the effect was stronger in subjects with a history of cardiovascular disease events (Li et al, 2020).…”
Section: Effects On Blood Pressurementioning
confidence: 68%
“…90%–95% of cases represent primary hypertension, which arises independently of other conditions, and is associated with lifestyle and genetic factors (Oparil et al, 2018). Hypertension is divided into categories depending on severity and risk of complications, and small reductions in blood pressure (such as 1 mmHg), even for those considered normotensive, can represent a significant improvement in multiple predicted health outcomes such as all‐cause mortality or cardiovascular disease‐related mortality (Li et al, 2020; Miller, Van Elswyk, & Alexander, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For diagnosis of T2D, the difference in effect size between a 1% (log OR 1% = 0.0005) and a 1.7% reduction in n-6 PUFA synthesis is negligible (log OR 1.7% = 0.00095). Put into perspective, within the UK Biobank where a high proportion of habitual fish oil intake was reported (31.2%) [32], we estimate that fewer than 0.03% of cases of T2D may be attributed to fish oil supplementation (population attributable risk).…”
Section: Resultsmentioning
confidence: 99%